Post-exposure prophylaxis with doxycycline to prevent sexually transmitted infections in men who have sex with men: an open-label randomised substudy of the ANRS IPERGAY trial. Issue 3 (March 2018) - Molina, Jean-Michel; Charreau, Isabelle; Chidiac, Christian; Pialoux, Gilles; Cua, Eric; Delaugerre, Constance; Capitant, Catherine; Rojas-Castro, Daniela; Fonsart, Julien; Bercot, Béatrice; Bébéar, Cécile; Cotte, Laurent; et al.
Summary: Background: Increased rates of sexually transmitted infections (STIs) have been reported among men who have sex with men. We aimed to assess whether post-exposure prophylaxis (PEP) with doxycycline could reduce the incidence of STIs. Methods: All participants attending their scheduled visit in the open-label extension of the ANRS IPERGAY trial in France (men aged 18 years or older having condomless sex with men and using pre-exposure prophylaxis for HIV with tenofovir disoproxil fumarate plus emtricitabine) were eligible for inclusion in this open-label randomised study. Participants were randomly assigned (1:1) at a central site to take a single oral dose of 200 mg doxycycline PEP within 24 h after sex or no prophylaxis. The primary endpoint was the occurrence of a first STI (gonorrhoea, chlamydia, or syphilis) during the 10-month follow-up. The cumulative probability of occurrence of the primary endpoint was estimated in each group with the Kaplan-Meier method and compared with the log-rank test. The primary efficacy analysis was done on the intention-to-treat population, comprising all randomised participants. All participants received risk-reduction counselling and condoms, and were tested regularly for HIV. This trial is registered with ClinicalTrials.gov number, NCT01473472 . Findings: Between July 20, 2015, and Jan 21, 2016, we randomly assigned 232 participants (n=116 in the doxycycline PEP group and n=116 in the no-PEP group) who were followed up for a median of 8·7 months (IQR 7·8–9·7). Participants in the PEP group used a median of 680 mg doxycycline per month (IQR 280–1450). 73 participants presented with a new STI during follow-up, 28 in the PEP group (9-month probability 22%, 95% CI 15–32) and 45 in the no-PEP group (42%, 33–53; log-rank test p=0·007). The occurrence of a first STI in participants taking PEP was lower than in those not taking PEP (hazard ratio [HR] 0·53; 95% CI 0·33–0·85; p=0·008). Similar results were observed for the occurrence of a first episode of chlamydia (HR 0·30; 95% CI 0·13–0·70; p=0·006) and of syphilis (0·27; 0·07–0·98; p=0·047); for a first episode of gonorrhoea the results did not differ significantly (HR 0·83; 0·47–1·47; p=0·52). No HIV seroconversion was observed, and 72 (71%) of all 102 STIs were asymptomatic. Rates of serious adverse events were similar in the two study groups. Gastrointestinal adverse events were reported in 62 (53%) participants in the PEP group and 47 (41%) in the no-PEP group (p=0·05). Interpretation: Doxycycline PEP reduced the occurrence of a first episode of bacterial STI in high-risk men who have sex with men. Funding: France Recherche Nord & Sud Sida-HIV Hépatites (ANRS) and Bill & Melinda Gates Foundation.